Ferritic stainless steel components for water facilities

A ferritic stainless steel with controlled composition and austenite transformation addresses corrosion and springback issues, providing durable and cost-effective solutions for water facilities with reduced plate thickness loss and high dimensional accuracy.

JP7607443B2Active Publication Date: 2024-12-27NIPPON STEEL METAL PROD CO LTD +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020195716
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-11-26
Publication Date
2024-12-27
Estimated Expiration
2040-11-26

AI Technical Summary

Technical Problem

Existing steel materials for water facilities, such as irrigation canals, face challenges with corrosion resistance in freshwater to brackish environments, high springback during forming, and require costly and complex equipment for manufacturing, leading to reduced durability and increased maintenance.

Method used

A ferritic stainless steel with a specific composition (C: 0.080% or less, N: 0.100% or less, Cr: 10.50% to 19.00%, and controlled austenite transformation rate of 15% or more) that offers excellent corrosion resistance and low springback, suitable for continuous forming using conventional equipment, ensuring high dimensional accuracy and durability up to 50 years.

Benefits of technology

The ferritic stainless steel exhibits superior corrosion resistance and shape fixability, maintaining high dimensional accuracy and reducing plate thickness loss to 0.042 mm/year over 50 years, suitable for water facilities without the need for complex equipment modifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607443000003
    Figure 0007607443000003
  • Figure 0007607443000001
    Figure 0007607443000001
  • Figure 0007607443000002
    Figure 0007607443000002
Patent Text Reader

Abstract

To provide a ferritic stainless steel member having excellent corrosion resistance in accordance with a corrosive environment from fresh water to brackish water, and favorable for an application to a water supply facility.SOLUTION: A ferritic stainless steel member for a water supply facility includes, by mass, 0.080% or less C, 0.100% or less N, 10.50 to 19.00% Cr, 0 to 2.00% Ni, 0 to 2.00% Mn, 0 to 2.00% Cu, 0 to 2.00% Mo, 0 to 0.50% Ti, 0 to 1.00% Nb, 0 to 0.50% Zr, 0 to 0.500% Sn, 0 to 0.500% Al, 0 to 1.00% Si, and the balance Fe with inevitable impurities, and a maximum value of an austenite transformation rate is 15% or more when heated to an Ac1 transformation point or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferritic stainless steel component for hydraulic facilities, which is made of ferritic stainless steel and is used in hydraulic facilities such as the banks of agricultural irrigation channels, and is suitable for use in lightweight steel sheet piles and steel molded components that come into direct contact with natural fresh water or brackish water. [Background technology]

[0002] Lightweight steel sheet piles, steel molded materials, and other hydraulic facility components are primarily used in civil engineering works in areas that are constantly in direct contact with natural fresh water or brackish water. To protect against corrosion from natural fresh water or brackish water, methods such as thickening steel sheet piles and other hydraulic facility components to allow for corrosion allowances, forming cathodic protection layers, and surface plating layers are used.

[0003] Normally, lightweight steel sheet piles are designed to withstand the above-mentioned corrosion and have a durability of about 30 years, but depending on the salt environment and location, corrosion may cause more than expected thinning. There are also many steel sheet pile revetments where corrosion has progressed to the extent that the steel base is exposed, holes have opened in the steel sheet pile revetment, and hollows have formed due to the suction of soil and sand.

[0004] With the objective of protecting the entire surface of a steel sheet pile revetment from corrosion, preventing thinning and holes due to corrosion of the steel sheet pile, and preventing hollowing due to the suction of soil and sand and ground subsidence, Patent Document 1 proposes a steel sheet pile revetment structure in which the front and back surfaces of the steel sheet pile are electrically protected from corrosion and a planar wave-dissipating belt is provided on the wave collision surface of the front of the steel sheet pile.

[0005] However, the current required for corrosion protection varies depending on the environment. In addition, a direct current greater than the corrosion current must be constantly applied, and the larger the scale of water facilities such as various irrigation canal revetments and retaining walls, the larger the scale of the current control equipment and devices becomes, which leads to a problem of increased power consumption required for the cathodic protection.

[0006] As described above, the invention disclosed in Patent Document 1 has a practical drawback in that it becomes more difficult to apply the invention to maintain and improve the corrosion resistance of hydraulic facilities used in various corrosive environments, from fresh water to brackish water, as the scale of the facilities and equipment increases.

[0007] Patent Document 2 discloses a technology for improving corrosion resistance in a submerged environment by forming a coating layer of epoxy resin or the like as an upper layer of a hot-dip plating layer, thereby improving the corrosion resistance of steel structures used in agricultural waterways, etc. It is believed that if a coating layer or coating layer as in Patent Document 1 is formed on carbon steel, the corrosion resistance of water facilities can be improved. However, since steel sheet piles are installed in the ground, there is a risk that the coating layer, and in some cases even the coating layer, may peel off or be damaged during construction, exposing the base steel. Furthermore, water facility components are generally heavy and are usually handled using heavy civil engineering machinery, so collisions and friction between components cannot be prevented, and localized loss of protective effect due to peeling or damage of surface protective layers such as coating and surface treatment layers is almost inevitable. In addition, there is a concern that the coating layer and surface plating may gradually wear away due to gravel contained in the flowing water on steep slopes. In order to avoid these, it is considered desirable to use stainless steel as a material with good corrosion resistance even on a bare surface.

[0008] Patent Document 3 discloses a technology for reducing life cycle costs and improving corrosion resistance by using stainless steel as the steel material for corrugated waterway components for agricultural irrigation channels, etc. Although the use of stainless steel is disclosed, it only discloses the JIS steel types that can be used, and it is difficult to say that stainless steel that is particularly suitable for irrigation facilities, taking into consideration optimization of the composition system from the perspective of corrosion resistance and durability according to the environment to which it will be exposed, or moldability and manufacturability according to the shape of the components, is disclosed.

[0009] Patent Document 4 discloses a freshwater ferritic stainless steel with excellent crevice corrosion resistance that can be applied to natural freshwater environments with low salt concentrations. Although this patent document discloses a specific component composition of the ferritic stainless steel, it requires 1% or more of V, an expensive element, and there are concerns about the cost. In addition, V is an element that is relatively easily oxidized at high temperatures, and the melting point of the oxide is low, so that ferritic stainless steels with a V content of more than 0.6% in particular have the problem of reduced manufacturability and significantly increased concerns about the occurrence of defects due to unavoidable high-temperature oxidation during the manufacturing process. Furthermore, even though stainless steel is generally ferritic, it has a large springback during plastic deformation processing such as press molding, bending, and roll forming compared to ordinary steel. Therefore, when stainless steel is molded under the same conditions as ordinary steel using ordinary steel equipment, there is a problem that dimensional accuracy is reduced and shape defects are likely to occur. However, Patent Document 4 does not take into consideration the improvement of shape defects and dimensional accuracy caused by elastic recovery during molding.

[0010] Carbon steel has traditionally been the main steel material used for hydraulic facility components. Therefore, in the future, it will be more economical to use carbon steel manufacturing facilities when applying stainless steel. To achieve this, there is a demand for stainless steel that can be continuously formed in carbon steel manufacturing facilities, even if it is relatively thick, and that has little spring back after forming. Furthermore, in the past, when ordinary steel was used in freshwater environmental waterways, the amount of corrosion was taken into consideration, and based on experience, the design thickness (product thickness) was set to the required thickness plus 2.0mm of thickness reduction due to corrosion, assuming use for 20 to 40 years. In other words, the thickness reduction is 0.05mm to 0.1mm per year. The required thickness is the thickness used in design (thickness that can be expected to have strength), and is the product thickness minus the thickness reduction due to corrosion. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2016-142080 A [Patent Document 2] JP 2017-179387 A [Patent Document 3] JP 2018-162594 A [Patent Document 4] Patent No. 4780846 Summary of the Invention [Problem to be solved by the invention]

[0012] The first object of the present invention is to provide a ferritic stainless steel component for hydraulic facilities which has excellent corrosion resistance suited to the corrosive environments of irrigation canals, from fresh water to brackish water, has little springback after forming, can be manufactured by continuous forming in the same way as carbon steel using conventional equipment, and is suitable for use as a component for hydraulic facilities. Since stainless steel has excellent corrosion resistance, it is possible to greatly reduce the thickness loss due to corrosion. However, a specific value had not been found. Furthermore, the thickness loss for a service life of 50 years had not been set. A second object of the present invention is to provide a ferritic stainless steel member for water facilities that can specify the thickness loss due to corrosion for a service life of 50 years or less. [Means for solving the problem]

[0013] The present inventors have discovered that as-hot-rolled ferritic stainless steel or ferritic stainless steel annealed after hot rolling, which has a Cr content of 10.50 to 19.00 mass%, has excellent corrosion resistance in a range of corrosive environments from fresh water to brackish water, and can also ensure toughness.

[0014] In addition, the present inventors c1 We have found that by setting the maximum amount of change to the austenite phase when heated to a temperature above a certain level, the processing accuracy when forming steel structural components for water facilities is significantly improved and manufacturing becomes easier. Furthermore, we have found that by appropriately designing the composition of the components and ensuring the required corrosion resistance, it is possible to obtain ferritic stainless steel components that are particularly suitable for application to water facilities.

[0015] The present invention has been made based on these findings, and the ferritic stainless steel component for water utilization facilities of the present invention is as follows.

[0016] (1) containing, by mass%, C: 0.080% or less, N: 0.100% or less, Cr: 10.50-19.00%, Ni: 0-2.00%, Mn: 0-2.00%, Cu: 0-2.00%, Mo: 0-2.00%, Ti: 0-0.50%, Nb: 0-1.00%, Zr: 0-0.50%, Sn: 0-0.500%, Al: 0-0.500%, Si: 0-1.00%, with the balance being Fe and impurities; A c1 A ferritic stainless steel component for water facilities, characterized in that the maximum austenite transformation rate when heated above its transformation point is 15% or more. (2) A ferritic stainless steel plate component for water facilities according to (1), characterized in that the reduction in plate thickness due to corrosion when used in a freshwater environment is 0.042 mm / year or less over a service life of 50 years or less. Effect of the Invention

[0017] According to the present invention, components made of ferritic stainless steel, which has excellent corrosion resistance in a range of corrosive environments from fresh water to brackish water and has high shape fixability, can be formed with high dimensional accuracy and is therefore suitable for use in water facilities. Furthermore, according to the present invention, it is now possible to set the thickness of stainless steel sheet piles for waterways to a service life of 50 years, something that was not possible before. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a diagram for comparing a cross-sectional shape (target cross-sectional shape) before springback when forming a steel sheet with a cross-sectional shape after springback after the forming. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described.

[0020] <Ingredients> First, the reasons for limiting the chemical composition of the stainless steel member of this embodiment will be described. Note that, unless otherwise specified, the notation of % in the chemical composition means % by mass.

[0021] [C:0.080% or less] Generally, C deteriorates formability, corrosion resistance, and weldability, so the lower the C content, the better. Therefore, from the viewpoint of ensuring corrosion resistance, the upper limit is set to 0.080%. From the viewpoint of corrosion resistance, the upper limit is preferably set to 0.020%. On the other hand, C is also an element that promotes and increases the formation of the austenite phase at high temperatures. c1 It is an important requirement that the maximum austenite transformation rate at temperatures above the 15% point be 15% or more, and in this respect, C is an effective element. In addition, since an excessive reduction in C content increases refining costs, the lower limit is preferably 0.002%, and more preferably 0.005%. In addition to C, elements that promote and increase the formation of the austenite phase at high temperatures include N, Ni, Cu, Mn, etc. In the present invention, it is possible to obtain a desired structure by adjusting the contents of these elements. Among these, C and N, which are usually treated as harmful elements, are the most economical elements, and this also saves on expensive metallic elements such as Ni, Cu, and Mn. In stainless steel, particularly ferritic stainless steel, C and N are usually regarded as harmful elements that reduce the formability, corrosion resistance, and weldability. In the present invention, however, C and N are also elements that are useful for minimizing springback and improving the dimensional accuracy and manufacturability of thick, continuously formed members through structural control by promoting the formation of austenite phase.

[0022] [N:0.100% or less] N is an element that increases the amount of austenite transformation, and is preferably contained in a balance with other elements to obtain such an effect. On the other hand, excessive content deteriorates formability, corrosion resistance, and weldability, so the upper limit is set to 0.100%. From the viewpoint of preventing formability, particularly an excessive increase in processing reaction force, the upper limit is preferably set to 0.050%. On the other hand, in ferritic stainless steels, N is usually considered harmful like C, but for the same reason as C as described above, the preferable lower limit is set to 0.002%. 0.005% or more is more preferable.

[0023] [Cr: 10.50~19.00%] Cr is an essential element for ensuring corrosion resistance. In order to form a passive film in the expected environment, 10.50% or more is necessary, and this is the lower limit. On the other hand, if it exceeds 19.00%, it will cause a decrease in workability at low temperatures and a deterioration in toughness, so 19.00% is the upper limit.

[0024] Furthermore, in the present invention, the following elements may be added in addition to the above composition.

[0025] [Ni: 0-2.00%] Ni is an element that is effective in suppressing the progression of pitting corrosion, and also has the effect of increasing the amount of austenite transformation. This effect is stably exhibited when added at 0.05% or more. It is also effective in improving the toughness of hot-rolled sheets. 0.10% or more is more effective, and 0.15% or more is even more effective. In addition, since Ni is an expensive element, adding a large amount not only increases costs, but also has the risk of increasing susceptibility to stress corrosion cracking, so the upper limit is set at 2.00%. Considering the alloy cost, the upper limit is preferably 0.60%.

[0026] [Mn: 0-2.00%] Mn is an element added as a deoxidizer. Its effect is manifested at 0.01% or more. However, excessive addition forms MnS and reduces corrosion resistance, so the upper limit is set to 2.00%. The preferred upper limit is 0.50%.

[0027] [Cu: 0-2.00%] Cu is an element that improves corrosion resistance. This effect is manifested at 0.05% or more. It is preferably 0.10% or more. On the other hand, if the Cu content is too high, hot workability is reduced and it may cause edge cracks during hot rolling, so the upper limit is set to 2.00%.

[0028] [Mo: 0-2.00%] Mo may be added as necessary to improve corrosion resistance, and in order to exert these effects, the lower limit is preferably set to 0.01%, more preferably 0.10%, and even more preferably 0.5%. On the other hand, excessive addition of Mo reduces workability, so the upper limit is set to 2.00%, and preferably 1.10%.

[0029] [Ti: 0-0.50%; Nb: 0-1.00%] Ti and Nb have the effect of fixing C or N and improving ductility during bending, but if the amount is small, the effect is weak, so it is preferable to add Ti and Nb in an amount of 0.01% or more. However, excessive addition not only leads to a decrease in ductility, but also increases costs and reduces manufacturability, so the upper limits are set at 0.50% for Ti and 1.00% for Nb.

[0030] [Zr: 0-0.50%] Zr is added as necessary because, like Nb and Ti, it forms carbonitrides and inhibits the formation of Cr carbonitrides, improving corrosion resistance. Furthermore, even if it is contained in excess of 0.50%, the effect is saturated and the formation of large oxides can cause surface defects, so it is preferable to add 0.50% or less. Since Zr is a more expensive element than Ti and Nb, it is preferable to set the lower limit of Zr to 0.02% and the upper limit to 0.30%, taking into account the manufacturing cost. It is more preferable to set it to 0.10% or less.

[0031] [Sn: 0~0.500%] Sn is an effective element for improving corrosion resistance without significantly deteriorating mechanical properties at room temperature. Although the effect on corrosion resistance can be obtained even with a small amount of addition, in order to obtain the full effect, it is preferable to contain 0.005% or more. More preferably, it is 0.010% or more. If the Sn content is too high, manufacturability and weldability deteriorate, so the upper limit is set to 0.500%.

[0032] [Al: 0-0.500%] Al is useful as a deoxidizing element, and its effect is manifested at 0.005% or more. However, excessive addition leads to a decrease in room temperature ductility, so the upper limit is set at 0.500%. If deoxidation can be achieved with other elements such as Si, Al does not need to be contained.

[0033] [Si: 0-1.00%] Silicon is an element useful as a deoxidizer and also improves oxidation resistance. In the present invention, it is not necessary for silicon to remain in the steel, but in order to obtain an adequate deoxidizing effect in the refining stage, 0.01% or more of silicon must remain. However, since silicon hardens the steel sheet, the upper limit is set to 1.00%. The preferred upper limit is 0.50%.

[0034] [P:0.040% or less] P is an element with a large solid solution strengthening ability, but is an impurity element that is harmful to corrosion resistance, so in the present invention, the lower the content, the better. Therefore, the upper limit is set to 0.040%. When better corrosion resistance is required, 0.030% or less is preferable. There is no lower limit, and the P content may be 0. However, since excessive reduction increases the dephosphorization load and increases the manufacturing cost due to the selection of low-P raw materials, 0.005% may be set as the substantial lower limit.

[0035] [S:0.0100% or less] Since S is an impurity element that forms sulfide-based inclusions and deteriorates the general corrosion resistance (general corrosion and pitting corrosion) of steel materials, the lower the content, the better. Therefore, the upper limit is set to 0.0100%. A preferred upper limit is 0.0050%. Also, the lower the S content, the better the corrosion resistance, so the content may be 0. However, since reducing S increases production costs due to increased desulfurization load and the selection of low-S raw materials, the practical lower limit may be 0.0001% or 0.0005%.

[0036] [Metal structure] The ferritic stainless steel constituting the ferritic stainless steel member of the present invention is A c1 The maximum austenite transformation rate when heated to a temperature above the c1 The maximum austenite transformation rate at a temperature above the specified point is 15% or more. By doing so, springback after the stainless steel is formed into steel structural components for water facilities is significantly reduced. In other words, when stainless steel is formed, elastic strain is released when the processed product is separated from the die, so the product angle becomes larger than the design angle. This characteristic related to springback is called shape fixability, and the inventors have determined that A c1 It was found that when the maximum austenite transformation rate when heated to a temperature above this point is 15%, the shape fixability is significantly improved compared to stainless steels with a maximum austenite transformation rate of less than 15%, and that this is also superior to carbon steels (SS400, etc.) that have traditionally been widely used for water facilities. Here, A c1 The maximum austenite transformation rate when heated above the transformation point is the maximum value when the steel plate constituting the steel component is heated to A c1 After heating to above the transformation point, specifically to 1100°C for example, and then quenching by water cooling, the martensite area ratio of the crystal structure of the cross section is measured at five points, and the maximum of the martensite area ratios at the five points is taken as the maximum austenite transformation ratio. c1 This is because the austenite that is produced by transformation when heated above the transformation point transforms into martensite by subsequent rapid cooling. c1The transformation temperature can be defined as the temperature at which the transformation from the ferrite phase to the austenite phase begins. c1 The transformation point is a temperature below 1100°C.

[0037] The shape of the steel structure of the water facility in freshwater or brackish water environment with salinity of about 500 ppm or less, which is the subject of the present invention, varies depending on the member such as steel sheet pile or U-shaped flume, and there are various types of each member. Since the springback amount generally varies depending on the plate thickness, pressure, bending radius, etc., it is necessary to design taking the springback amount into consideration according to the shape of the processed product and the forming conditions. However, since the ferritic stainless steel constituting the ferritic stainless steel member of the present invention has excellent shape fixability, it can be easily used for steel structural members of water facility of various shapes. In order to obtain such an effect, as described above, the maximum value of the austenite transformation rate needs to be 15% or more, and more preferably 30% or more. The upper limit is 100%.

[0038] The maximum austenite transformation rate can be controlled by designing the composition while considering the balance between ferrite-forming elements and austenite-forming elements. In the present invention, the main austenite-forming elements are C, N, Ni, Mn, and Cu, and the main ferrite-forming elements are Cr, Si, Mo, and Al. In the present invention, it is essential to design the composition within the above-mentioned composition range so that the maximum austenite transformation rate is 15% or more while ensuring the corrosion resistance required for hydraulic facilities. Within the composition range specified in the present invention, the more the austenite-forming elements and the less the ferrite-forming elements, the higher the maximum austenite transformation rate.

[0039] Furthermore, hot-rolled sheets of ferritic stainless steels that have been adjusted to undergo such structural changes have the property of being less susceptible to brittle cracking even at room temperature or lower.

[0040] <Thickness reduction due to corrosion> As mentioned above, the reduction in thickness due to corrosion of ordinary steel when used in freshwater environmental waterways is assumed to be 0.05 mm to 0.1 mm per year, assuming a 20 to 40 year period of use. In contrast, the reduction in thickness during long-term use was investigated for the ferritic stainless steel members for water facilities of the present invention.

[0041] Using steel plate 1 shown in Tables 1 and 2 described below, a one-year freshwater environment exposure test was carried out using coupon test pieces. In evaluation 1, the thickness loss over one year (average thickness loss within the sample) was evaluated from the change in mass of the test piece. As a result, the average thickness loss within the sample over one year was 0.8 μm. Regarding the average thickness loss within the sample, the average thickness loss within the sample per year when considering 50 years of use is considered to be the same as the average thickness loss within the sample over one year mentioned above. For evaluation 2, the maximum corrosion depth of the test piece after one year was evaluated. For the maximum corrosion depth, the √ law of the number of years passed was assumed to hold, and the maximum corrosion depth after 50 years was calculated from the maximum corrosion depth after one year, which was converted into a loss of thickness of 2.1 mm. Therefore, the average loss of thickness per year over the period was calculated to be 0.042 mm / year (= 2.1 / 50).

[0042] The plate thickness loss obtained in the above evaluation 2 can be evaluated as the upper limit of plate thickness loss for a service life of 50 years. Therefore, in the present invention, the plate thickness loss due to corrosion when used in a freshwater environment is specified to be 0.042 mm / year or less for a service life of 50 years or less. Assuming a 50-year use, the maximum plate thickness loss due to corrosion can be 2.1 mm (0.042 x 50) in 50 years. On the other hand, the thickness reduction obtained in the above Evaluation 1 (0.0008 mm / year (0.8 μm / year)) can be evaluated as the lower limit of thickness reduction over a service life of 50 years.

[0043] <Thickness> The ferritic stainless steel member of the present invention preferably has a plate thickness of 3.0 mm or more. If the plate thickness is less than 3.0 mm, it is too thin to obtain sufficient rigidity, and there is a risk that the rigidity and strength required for water facilities such as retaining walls may not be ensured. In addition, in order to ensure the rigidity of the member, it will be necessary to design a complex cross-sectional shape, and to design a molding device to realize it, and to consider additional new equipment and technologies, such as processing and molding technology.

[0044] <Manufacturing method> The ferritic stainless steel member of the present invention is a product of processing and forming a hot-rolled or hot-rolled annealed steel sheet of a ferritic stainless steel having the above-mentioned composition and the above-mentioned austenitic transformation rate, and is formed into a predetermined product shape through the steps of melting, casting, hot rolling, and pickling. If necessary, the product may be formed into the product shape of the ferritic stainless steel member of the present invention by annealing after hot rolling. There is no particular restriction on the equipment, and conventional manufacturing equipment can be used. The ferritic stainless steel used in the stainless steel member of the present invention is manufactured, stored, and transported in the form of a coil, like a normal stainless steel strip.

[0045] The hot rolling conditions are not particularly specified, but the slab heating temperature is preferably 1100°C to 1250°C. The hot rolling finish temperature is preferably 850°C or higher. Furthermore, when winding the hot rolled slab into a coil, accelerated cooling to 350°C can be performed immediately after the hot rolling finish reduction by spraying water or air water cooling, if necessary. Furthermore, forced cooling after winding into a coil is not necessary.

[0046] When annealing is performed, the annealing temperature is 680 to 930°C (A of the relevant steel composition). c1 A c1 If the temperature exceeds this point, martensite may form, making the material brittle and hard, and the crystal grains may become coarse, which is undesirable. c1 Although the points fluctuate, annealing is A c1 It is necessary to carry out the annealing in the α single phase region just below the point. In general, the annealing temperature for BAF annealing is about 680 to 900°C.

[0047] The ferritic stainless steel member of the present invention is obtained by forming the above-mentioned hot-rolled steel sheet or hot-rolled annealed steel sheet, and is suitable for use in water facilities such as the bank protection of agricultural irrigation channels. The ferritic stainless steel member of the present invention is particularly used as a formed structural member such as a lightweight steel sheet pile, a waterway member such as a U-shaped gutter, a panel for stainless steel panel covering construction, a corrugated member, and has excellent corrosion resistance in an environment in direct contact with natural fresh water or brackish water.

[0048] The effects of the present invention will be described below with reference to examples, but the present invention is not limited to the conditions used in the following examples. EXAMPLES

[0049] In this example, steel having the composition (mass%) shown in Table 1 was melted and cast into an ingot, which was then heated to 1150 to 1230°C, and then hot rolled to a thickness of 5 mm at a finishing temperature in the range of 880 to 980°C to obtain a hot-rolled steel sheet. For examples in which the manufacturing conditions in Table 1 indicate "as hot-rolled", quality evaluation was performed as is. For examples in which the manufacturing conditions in Table 1 indicate "hot-rolled annealed", the above-mentioned hot-rolled steel sheet was further subjected to hot-rolled annealing at 850 to 1000°C, and quality evaluation was performed using the hot-rolled annealed steel sheet.

[0050] The maximum austenite transformation rate was measured by cutting the ferritic stainless steel plate obtained in the above example into a 30 mm square test piece at 1100°C (A C1 The specimens were heated at 1100°C (above the rolling point) for 10 minutes and then quenched in water. The specimens were then cut in the thickness direction parallel to the rolling direction, and the cross sections were etched with aqua regia for microstructural observation. Microstructural observation was carried out at five random locations in the center of the thickness (within the range of 2-4 mm depth from the surface). Since austenite formed by transformation when heated to 1100°C transformed into martensite by quenching, the proportion of the area of ​​martensite to the total area of ​​the observation field was measured in the microstructural observation of the cross section of the specimen after cooling, and this was defined as the A C1The austenite transformation rate was determined as the austenite transformation rate when the specimen was heated to above the γ transformation point. Image analysis was performed using the image processing software Image J. The maximum area ratio (%) of martensite in the five microstructural observations was determined as the maximum austenite transformation rate, and is shown in the "Maximum γ transformation rate" column in Table 2.

[0051] The steel sheets manufactured under the above-mentioned manufacturing conditions were subjected to a shape fixability evaluation test, a formability test, and a toughness test, and were compared with ordinary steel SS400. The results are shown in Table 2.

[0052] In Table 2, the evaluations of shape fixability, formability and toughness in comparison with SS400 are expressed as follows. (i) Shape fixability was evaluated by forming a cross-sectional shape simulating a lightweight steel sheet pile into the shape shown by the dotted line in Figure 1 and measuring the amount of springback (ΔL2). In this forming test, the bending ridge of the test piece plate was parallel to the hot rolling L direction (rolling direction) (i.e., Figure 1 corresponds to a cross-sectional view seen from the hot rolling rolling direction), and the width of the test piece plate was 55 mm ± 5 mm. Compared to SS400, ΔL2 values ​​that are the same are indicated by "+", and values ​​that are smaller (superior) are indicated by "++". (ii) Formability was evaluated by bending three test pieces (n=3) at room temperature, 300 mm long, 60 mm wide, with edges hand-polished with #80 sandpaper, in the hot-rolled C direction with a bending radius of 1t ("t" = plate thickness), at 180°. If no cracks occurred, they were marked with an "O"; if even one crack occurred, even if it was partial, they were marked with an "X."

[0053] The toughness was evaluated by a Charpy impact test in accordance with JIS Z 2242. The test piece with a V-notch sub-size was used to obtain a Charpy impact value of 30 J / cm at 0°C. 2 If the condition is met, it is indicated by “○”, and if not, it is indicated by “×”.

[0054] [Table 1]

[0055] [Table 2]

[0056] The ferritic stainless steel members of the present invention were shown to have excellent shape fixability, i.e., excellent formability, even when compared with SS400, a common ordinary steel that is most commonly used in the water facilities that are the subject of the present invention. [Industrial Applicability]

[0057] According to the present invention, it is possible to provide a ferritic stainless steel member suitable for water facilities that are constantly in direct contact with natural fresh water or brackish water, such as the bank protection and retaining walls of rivers and various irrigation channels, and to provide an optimal reduced plate thickness for a service life of 50 years or less.

Claims

1. In mass percent, C: 0.080% or less, N: 0.100% or less, Cr: 10.50-19.00%, Ni: 0-2.00%, Mn: 0 to 2.00%, Cu: 0-2.00%, Mo: 0-2.00%, Ti: 0 to 0.50%, Nb: 0 to 1.00%, Zr: 0 to 0.50%, Sn: 0-0.500%, Al: 0-0.500%, Si: 0 to 1.00%, with the balance being Fe and impurities; A c1 A ferritic stainless steel component for water utilization facilities, characterized in that the maximum austenite transformation rate when heated above its transformation point is 15% or more.

2. 2. A ferritic stainless steel member for water facilities according to claim 1, characterized in that the reduction in plate thickness due to corrosion when used in a freshwater environment is 0.042 mm / year or less for a service life of 50 years or less.

Citation Information

Patent Citations

  • Method of manufacturing ferritic stainless steel sheet excellent in ductility, workability and ridging resistance

    JP2001089815A

  • Method for selecting stainless steel for water section equipment

    JP2005320574A

  • Ferritic free-cutting stainless steel

    JP2008274361A

  • Ferritic stainless steel having excellent local corrosion resistance

    JP2010248625A

  • Stainless steel pipe joint

    JP2013204741A